The Design of Memristor Based High Pass Filter Circuit - Sahin, Muhammet Emin; Guler, Hasan (Ieee, 2017)
Many researchers accept to memristor as fourth basic circuit elements in literature. The missing linkage between charge and flux is provided by a device which is memristor. The memristor (memory resistor) is formally defined as a two-terminal element in which the magnetic flux between the terminals is a function of the amount of electric charge that has passed through the device. It is predictable that memristor-based analog filters will provide different features from other circuit devices. In this paper, we use an emulator circuit which seems memristors property basic to explain the high pass filter with memristor. Firstly, an emulator existing in literature is used fort his application. Then, memristor-based high pass analog filter is modeled, filter waveforms and performance analyzed in time and frequency with simulations. Circuit gain and phase results are explained. These results obtained in this study can be used in the design of memristor-based high pass filter.
24th IEEE International Conference on Electronics, Circuits and Systems (ICECS) -- DEC 05-08, 2017 -- Batumi, GEORGIA
Keywords: memristor; emulator; filter; multisim